2021
DOI: 10.1186/s12935-021-02339-3
|View full text |Cite
|
Sign up to set email alerts
|

Let-7a induces metabolic reprogramming in breast cancer cells via targeting mitochondrial encoded ND4

Abstract: Background and objectives MicroRNA (miRNA) that translocate from the nucleus to mitochondria are referred to as mitochondrial microRNA (mitomiR). Albeit mitomiRs have been shown to modulate gene expression, their functional impact within mitochondria is unknown. The main objective of this study is to investigate whether the mitochondrial genome is regulated by miR present inside the mitochondria. Methods and results Here, we report mitomiR let-7a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…The main aim of these 12 studies [ 38 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] was to comprehensively analyze the metabolic balance and/or chemoresistance associated with miRNAs in different cancers. In nine studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], the aim was to investigate the effect of miRNAs on mitochondrial function in cancer tissues and cell lines. Five studies [ 64 , 65 , 66 , 67 , 68 ] reported an the association between miRNAs and the regulation of glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aim of these 12 studies [ 38 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] was to comprehensively analyze the metabolic balance and/or chemoresistance associated with miRNAs in different cancers. In nine studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], the aim was to investigate the effect of miRNAs on mitochondrial function in cancer tissues and cell lines. Five studies [ 64 , 65 , 66 , 67 , 68 ] reported an the association between miRNAs and the regulation of glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies conducted during the search period reported 21 miRNAs with tumor suppressive actions: miR-let-7a [ 44 , 55 ], miR-1 [ 56 ], miR-17* [ 73 ], miR-17-3p [ 74 ], miR-24-2 [ 77 ], miR-27a [ 45 ], miR-34a-5p [ 63 ], miR-125b [ 46 , 47 ], miR-128 [ 64 ], miR-133a [ 48 ], miR-140-5p [ 65 ], miR-195 [ 57 , 70 , 77 ], miR-200a [ 58 ], miR-223 [ 75 ], miR-340 [ 71 ], miR-342-3p [ 49 ], miR-365-2 [ 77 ], miR-519d [ 76 ], miR-663 [ 59 ], miR-1291 [ 72 ], and miR-4485 [ 60 ]. Of these studies, 20 were in breast cancer, 1 was in lung cancer and osteosarcoma, 2 were in melanoma, 2 were in prostate cancer, and 1 was in pancreatic cancer ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…By means of immunoprecipitation assays, it has been demonstrated that mitochondrial miRNAs also function by directly interacting with target mRNAs in an Ago2-dependent manner [ 15 , 26 , 34 , 35 , 36 ]. However, unlike cytosolic miRNAs which are well characterized to negatively regulate gene expression, the molecular effects of mitochondrial miRNAs were controversial; some can promote the translation of target mRNAs without affecting their level.…”
Section: Mitochondrial Mirnasmentioning
confidence: 99%
“…For instance, miR-378 targets ATP6 mRNA to decrease ATP6 level and ATP production in cardiomyocytes [ 15 , 31 ]. Let-7a post-transcriptionally inhibits ND4 by directly binding its mRNA to alter the activity of Complex I in breast cancer cells [ 36 ]. MiR-1 targets ND1 and COX1 mRNA to enhance their translation and ATP production in muscle cells [ 34 ].…”
Section: Mitochondrial Ncrnas Mediate Mitochondrial Homeostasismentioning
confidence: 99%
“…Moreover, down-regulated miR-125a-5p has been revealed to promote the reprogramming of glucose metabolism and cell malignancy by increasing levels of cd147 in thyroid cancer [65] . Furthermore, Let-7a has been found to induce metabolic reprogramming in breast cancer cells via targeting mitochondrial encoded NADH dehydrogenase subunit 4 (ND4) [66] .…”
Section: Mirna Mediated Cancer Cell Reprogramming: Emerging Alternativesmentioning
confidence: 99%